2012
DOI: 10.1080/02786826.2012.659360
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical Description of Experimentally Determined Charge Distributions of a Unipolar Diffusion Charger

Abstract: The charge distributions of an improved opposed flow unipolar diffusion charger were measured using a tandem differential mobility analyzer (DMA) set up in a size range of approximately 20-400 nm. The charger is intended to be used in a portable aerosol sizer to measure particle size distributions. The determined charge distributions were represented by lognormal distributions, and a set of equations and coefficients was developed to calculate the charge distributions. These equations can be easily implemented… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 38 publications
1
3
0
Order By: Relevance
“…As in earlier studies (e.g., J€ arvinen et al 2017; Kaminski et al 2012) the charge distribution was found to closely follow a log-normal distribution. Therefore, the geometric mean was selected as a suitable indicator for the charging efficiency, rather than arithmetic mean.…”
Section: Achieved Charging Statessupporting
confidence: 83%
“…As in earlier studies (e.g., J€ arvinen et al 2017; Kaminski et al 2012) the charge distribution was found to closely follow a log-normal distribution. Therefore, the geometric mean was selected as a suitable indicator for the charging efficiency, rather than arithmetic mean.…”
Section: Achieved Charging Statessupporting
confidence: 83%
“…All of the instruments are based on electrical diffusion charging of the particles and hence follow the same measurement principle. The rationale behind these instruments is that the electrical diffusion charging of submicron particles is approximately proportional to d p 1.13 (Jung & Kittelson, 2005;Asbach et al, 2011;Kaminski et al, 2012) and hence shares the same size dependence with the lung deposited surface area of spherical particles in the size range from approximately 40 to 200 nm and agrees within 730% between 20 and 400 nm (see Fig. 1).…”
Section: Instrumentationmentioning
confidence: 94%
“…They all follow the same basic principle as the SMPS (see Section 5.3), i.e., they use a particle charger to obtain a predictable particle charge distribution, a DMA to classify particles based on their electrical mobility and a miniaturized CPC to measure the concentration of the mobility classified particles. Furthermore, the dependence of the electrical mobility on the particle size gets weaker with increasing particle diameter, because in Eqn (2), the number n of elementary charges e is almost proportional to the particle diameter [48,49,51] and hence the dependence of the electrical mobility on particle diameter mainly stems from the Cunningham slip correction factor. To simplify the handling of the instruments, they are equipped with electrical chargers instead of radioactive or X-ray neutralizers.…”
Section: Instruments For Measuring Number Size Distributionmentioning
confidence: 99%